PENGARUH KOMPENSASI DAN PENDIDIKAN TERHADAP KINERJA KARYAWAN DI HOTEL CITY LUBUKLINGGAU - Suwarno Suwarno; Catur Windaryadi; Sudariyanto Sudariyanto (Jurnal Media Ekonomi (JURMEK), 2018)
This study aims to determine the effect of compensation and education on employee performance in City Lubuklinggau hotels. The time of the study was carried out for 9 months from November 2017 to August 2018. The population in this study was all employees employed at Lubuklinggau City City Hotels, which amounted to 35 people with saturated sampling. The study sample was 35 people. Data collection techniques in this study using observation, documentation and questionnaire. The analysis technique uses simple regression analysis, correlation test, determination test, t test and F test. Based on the results of data analysis and discussion that has been described in the previous chapter, it can be concluded that based on the results of t test calculations can be explained, that the Compensation Variable (X1 ) to Performance (Y) shows the value of tcount = 2,308 is greater than the value of t table (2,032) with a significance level of sig. = 0.05. This means that partially variable there is a significant effect of compensation on employee performance in City Lubuklinggau hotels. Based on the results of t-test calculations, that Educational Variable (X2) on Performance (Y) shows the value of tcount = 3.409 greater than the value of t table (2.032) with a significance level of sig. = 0.005. This means that partially there is a significant effect of education on employee performance in City Lubuklinggau hotels. Based on the Fcount test recapitulation, the Fcount value is 10,513> Ftable = 3.28 and the level of significance simultaneously sig F is 0,000. This shows that together (simultaneous) independent variables of research (Compensation and Education) have a significant influence on the dependent variable (Performance)